TINJAUAN YURIDIS TERHADAP PELAKSANAAN PERPARKIRAN DI KOTA SAMARINDA MENURUT PERATURAN DAERAH NOMOR 5 TAHUN 2015 TENTANG PENGELOLAAN DAN PENATAAN PARKIR - Ibrahim Ibrahim (Journal of Law ( Jurnal Ilmu Hukum ), 2021)
AbstractThis study is entitled "JURIDICIC REVIEW OF PARKING IMPLEMENTATION IN THE CITY OF SAMARINDA ACCORDING TO REGIONAL REGULATION NUMBER 5 OF 2015 CONCERNING MANAGEMENT AND ADMINISTRATION OF PARKING". regarding Parking Management Strategy (On The Street) by the Samarinda City Transportation Office in terms of Management of Public Roadside Parking, Management of Wild Parking, Dimensions of Increasing Local Revenue (PAD), and Dimensions of Smooth Traffic Flow. Data collection techniques are carried out through library research and field research, namely observation, direct interviews with informants, archives, and documents related to research. Whereas determining the source of the data is done by using purposive sampling techniques tailored to the study's objectives and accidental sampling techniques. Data analysis in this study uses descriptive qualitative methods of interactive model data analysis, which begins with the process of data collection, data simplification, data presentation, and withdrawal conclusion. From the results of the study obtained a picture that is the problem of parking carried out several strategies for managing public roadside parking namely by; First, the arrangement of permitted road sections for parking, which already includes the location and parking so that disruption to the smooth flow of traffic can be minimized, Second Optimizes the utilization of existing parking facilities, Third Provision of parking facilities outside the road body, especially in trade areas, services and offices and places of entertainment or recreation, Fourth Addition of item requirements in proposing a building permit (IMB) regarding the provision of parking facilities. In terms of evaluating parking management policies/strategies namely; First, what is done in setting the target by the Regional Revenue Service that only prioritizes the increase in regional income but not on the smooth flow of traffic and also the realization of the target. Second, namely the existence of a policy regarding mandatory tickets implemented by the UPTD parking management Samarinda City Transportation Office where the policy requires administrative evidence that is a ticket on parking activities at every parking point in the city of Samarinda. Third, the government policy in favor of parking management third party and cooperating with Primkopad Kartika Cooperative Aji Mustika Korem to help in increasing regional income and fostering all illegal parking attendants in Samarinda city. In xi, the legislation or law is conceptualized as a rule or norm that is a benchmark of human behavior that is considered appropriate. The findings obtained from this study include the Regional Parking Company has a role and function in minimizing congestion. This function is regulated based on regulations governing parking following the order of the legislation, in which there is a peak regulation / main regulations in the form of a law, namely Law Number 5 of 1965 concerning Regional Enterprises, then as the implementation, it is regulated in Regional Regulation Number 5 the Year 2015 and also in the form of Samarinda Mayor Decree which supports in terms of public roadside parking which is actually able to control illegal parking which is directly related to minimizing traffic congestion. But some things are actually regulated in rules but are not maximized in their authority. The factors that directly affect the function of Samarinda Parking are road factors and road body use, vehicle factors, road user awareness factors, and spatial regulation of parking space provision.Keywords: Parking